(3GdeaQGM aj TQM eQGM GdCQhGMs - (3MSf Hf MSjf GdLdjdis; (3UGMH GdeQGM , CMeO Hf Ydj Hf eSYhO, MSGe GdOjf CHh GdaVGFd,J (B700 (3g` s ((3CSYO s)
(3ChdgG (B:s
(3hHYO aEf GdcJGH GdeSei HQhGM GdCQhGM s
(3BNQgG (B:s
(3Ydi eUWai CRci GdSdGe hGcedG hGYWg jG QH GdhSjdI s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B175s
Keywords: (3GdUQas